2015
DOI: 10.1111/jnc.13405
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of levetiracetam target xCT in astrocytes in parkinsonian mice

Abstract: Astrocytes but not neurons express cystine/glutamate exchange transporter (xCT), which takes up cystine, and consequently supplies the substrate for GSH synthesis in neurons. It is recognized that GSH synthesis in neurons is dependent on the expression of xCT in astrocytes. Previous studies reported that levetiracetam (LEV), an anti-epileptic drug, increased xCT expression in vivo. The purpose of this study was to examine neuroprotective effects of LEV in parkinsonian models and demonstrate xCT in astrocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…One possibility is that the upregulation of xCT might be a compensatory protective reaction to increased oxidative stress. Consistent with this idea, treatments that elevate neuronal levels of GSH show protection in a variety of PD models [36,37]. On the other hand, as an exchanger, xCT elevates extracellular levels of glutamate that in turn may have toxic effects on dopaminergic neurons via glutamate receptors.…”
Section: Xct/slc7a11 Is Induced In Pd Cellular Modelsmentioning
confidence: 83%
“…One possibility is that the upregulation of xCT might be a compensatory protective reaction to increased oxidative stress. Consistent with this idea, treatments that elevate neuronal levels of GSH show protection in a variety of PD models [36,37]. On the other hand, as an exchanger, xCT elevates extracellular levels of glutamate that in turn may have toxic effects on dopaminergic neurons via glutamate receptors.…”
Section: Xct/slc7a11 Is Induced In Pd Cellular Modelsmentioning
confidence: 83%
“…Repeated injections of the anti‐epileptic agent, zonisamide (benzo[d]isoxazol‐3‐ylmethanesulfonamide), into 6‐hydroxydopamine (6(OH)DA)‐treated mice improve the cardinal symptoms of PD (Asanuma et al ., ) by increasing GSH through enhanced activity of the x c − exchanger. Similar results using levetiracetam have recently been reported (Miyazaki et al ., ). On the other hand, Massie and colleagues observed that mice lacking the xCT subunit of the x c − exchanger were less susceptible to toxicity by 6(OH)DA, possibly because of reduced glutamate release (Massie et al ., ).…”
Section: Thiol‐based Redox Therapies In Neurodegenerative Diseasementioning
confidence: 97%
“…xCT (the cysteine/glutamate exchanger) seems to be another. 11) Besides these amino acid transporters, organic ion transporters are also promising candidates as drug-targetable astrocyte transporters. Unlike the above-mentioned astroglia-specific transporters, the expression of organic ion transporters is not always limited to astrocytes (as described later); therefore, their potential as a pharmacological target in astrocytes has yet to be established.…”
Section: 7)mentioning
confidence: 99%